PROBLEMATIKA DALAM PELAKSANAAN PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DI KOTA PADANG - Eka Susanti (JCH (Jurnal Cendekia Hukum), 2020)
One type of tax is the Cost of Acquisition of Land and Building Rights (BPHTB). In Padang City, based on Regional Regulation Number 1 of 2011 and Regulation of Mayor Number 27 of 2016, the BPHTB tax collection system is different where the BPHTB collection system is not cohorence with the implementation of basic tasks and is determined by the parties as regulated by the function of increasing development activities in all fields. The research problems in this article are: 1) How is the collection of BPHTB in Padang City 2) How the verification process the land and building and constraints was receipts from land and building rights to the certificate of together in Padang City? 3) Are efforts of the government of padang in obstacles as receipts from land and building rights to the certificate of together in Padang City ? The research uses empirical juridical research methods. Primary data and secondary data obtained through literature study and interviews with research subjects. The results shows that the implementation of BPHTB collection in Padang city was carried out based on the Mayor Regulation No. 27 of 2016 and there are differences in tax collection regulated by Regional Regulation Number 1 of 2011, namely in the Cost of Acquisition (NPOP) assessment and collection system based on market prices, not transaction prices regulated in Bylaw No. 1 of 2011. The differences create legal uncertainty for the community. The obstacle that arises in the collection of Padang city BPHTB is the lack of taxpayer knowledge about BPHTB.